Hippocampal 5‐HT7 receptors signal phosphorylation of the GluA1 subunit to facilitate AMPA receptor mediated‐neurotransmission in vitro and in vivo. (21st March 2016) - Andreetta, Filippo; Carboni, Lucia; Grafton, Gillian; Jeggo, Ross; Whyment, Andrew D; van den Top, Marco; Hoyer, Daniel; Spanswick, David; Barnes, Nicholas M
Abstract : Background and Purpose: The 5‐HT7 receptor is a GPCR that is the target of a broad range of antidepressant and antipsychotic drugs. Various studies have demonstrated an ability of the 5‐HT7 receptor to modulate glutamatergic neurotransmission and cognitive processes although the potential impact upon AMPA receptors has not been investigated directly. The purposes of the present study were to investigate a direct modulation of the GluA1 AMPA receptor subunit and determine how this might influence AMPA receptor function. Experimental Approach: The influence of pharmacological manipulation of the 5‐HT7 receptor system upon phosphorylation of GluA1 subunits was assessed by Western blotting of fractionated proteins from hippocampal neurones in culture (or proteins resident at the neurone surface) and the functional impact assessed by electrophysiological recordings in rat hippocampus in vitro and in vivo . Key Results: 5‐HT7 receptor activation increased cAMP and relative pCREB levels in cultures of rat hippocampal neurones along with an increase in phosphorylation (Ser845) of the GluA1 AMPA receptor subunit evident in whole neurone extracts and within the neurone surface compartment. Electrophysiological recordings in rat hippocampus demonstrated a 5‐HT7 receptor‐mediated increase in AMPA receptor‐mediated neurotransmission in vitro and in vivo . Conclusions and Implications: The 5‐HT7 receptor‐mediated phosphorylation of the GluA1 AMPA receptor provides a molecular mechanism consistent with the 5‐HT7 receptor‐mediated increase in AMPA receptor‐mediated neurotransmission.